GE_GERICHTE P/22642/2022 vom 3. September 2024 - GE Cour de justice (2024)
ORDONNANCE DE CLASSEMENT;VIOLATION DE DOMICILE;POUVOIR DE REPRÉSENTATION;LÉSÉ | CPP.382.al1; CPP.319.al1.letb; RaLA.10.al1; CP.186